Clivus Chordoma: Case Report and Current Considerations on Endoscopic Endonasal Trans-Sphenoid Surgery with Neurosurgeon-Otolaryngologist Collaboration - Lekatompessy, Michael; Widyakrisna, Albertus Boyke Raditya; July, Julius (Medicinus, 2024)
Chordomas, infrequent malignancies primarily located along the craniospinal axis, showcase gradual growth and localized bone destruction, with the clival region involved in approximately 25-35% of cases. Headaches accompanied by neurological deficits are the typical clinical presentations. Complete surgical resection is the mainstay, with recent collaborative efforts between otorhinolaryngologists and neurosurgeons leading to a positive shift from traditional craniotomic procedures to endoscopic endonasal approaches, fostering minimally invasive techniques and utilizing endoscopy for primary visualization across the neuraxis. Furthermore, the concept of team surgery has been introduced, involving simultaneous contributions from ENT surgeons and Neurosurgeons at all stages of the procedure, including the approach, resection, and reconstruction phases. This report presents a series of two successful cases of clival chordomas managed using the endoscopic endonasal approach at Siloam Hospital Lippo Village This indicates its potential as a viable surgical choice, particularly within medical centers that possess the necessary specialties. Successful implementation is notably enhanced through collaborative efforts between otolaryngologists and neurosurgeons, underscoring the significance of interdisciplinary teamwork.